1969
DOI: 10.1080/00288233.1969.10421186
|View full text |Cite
|
Sign up to set email alerts
|

A study of the pattern of sulphur responses shown by dryland lucerne on some brown-grey earths

Abstract: Field trials showing apparently anomalous lack of response to sulphur topdressing of dryland lucerne on brown-grey earths in the Maniototo basin, Central Otago, were followed up by soil studies.Soil analyses showed the presence of sulphate in the deeper layers (2 to 4 ft) of the non-responsive soils, but no such accumulations were present in the responsive soils.Sulphur concentrations in lucerne from the non-responsive soils were normal (0.19% S or greater), but lucerne from the responsive soils had lower sulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1977
1977
1993
1993

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…There appears to be little that can be done to recover the K except possibly using deep-rooting plants such as lucerne. Blakemore et al (1969) have shown that lucerne can recover SO; from a considerable depth and possibly this plant could also recover K from deeper soil.…”
Section: Downward Movement Of Potassiummentioning
confidence: 99%
“…There appears to be little that can be done to recover the K except possibly using deep-rooting plants such as lucerne. Blakemore et al (1969) have shown that lucerne can recover SO; from a considerable depth and possibly this plant could also recover K from deeper soil.…”
Section: Downward Movement Of Potassiummentioning
confidence: 99%
“…Lucerne, however, is a deep-rooting plant and there is evidence that it can obtain significant amounts of nutrients from subsoil horizons. Blakemore et al (1969) attributed an apparent lack of response of dryland lucerne to sulphur applications, 011 …”
Section: Received 1 November 1976mentioning
confidence: 99%
“…The competitive advantage of phosphate over sulphate is implicit in the methods commonly used to extract adsorbed sulphate from soils. Salts and dilute acids of weakly (non-specifically) adsorbed anions, such as Cl and N03-, extract essentially only water-soluble S04 2 -(e.g., White 1959;Williams & Steinbergs 1959;Chao 1964;Roberts & Koehler 1968;.Blakemore et al 1969;Carson et al 1972;Tabatabai & Bremner 1972a;Westerman 1974;Saunders & Cooper 1975). To remove adsorbed sulphate from strongly anion-retentive soils, phosphates, or other specifically adsorbed anions (e.g., hydroxyl, fluoride), are required (e.g., Ensminger 1954;Fox et al 1964;Barrow 1967a;Blakemore et al 1968: Bromfield 1972 .…”
Section: Sulphate-phosphate Interactionsmentioning
confidence: 96%
“…The legume Lotus pedunculatus grew well despite a low content of adsorbed sulphate in the topsoil, probably because of its ability to tap the much greater reserves of sulphate in the subsoil. In an extreme example, Blakemore et al (1969) demonstrated the ability of dryland lucerne to obtain soluble S04 from depths of 100 em or more in some brown-grey earths of Central Otago, whereas the upper soil horizons were extremely S deficient.…”
Section: Profile Distrihutionmentioning
confidence: 97%
See 1 more Smart Citation